Cool to be Smart or Smart to be Cool? Understanding Peer Pressure in Education. (25th May 2018) - Bursztyn, Leonardo; Egorov, Georgy; Jensen, Robert
Abstract: We model and test two school-based peer cultures: one that stigmatizes effort and one that rewards ability. The model shows that either may reduce participation in educational activities when peers can observe participation and performance. We design a field experiment that allows us to test for, and differentiate between, these two concerns. We find that peer pressure reduces takeup of an SAT prep package virtually identically across two very different high school settings. However, the effects arise from very distinct mechanisms: a desire to hide effort in one setting and a desire to hide low ability in the other.